The Influence of Budget Planning and Budget Evaluation on Performance Accountability in the Disporapar of Sukabumi City - Ramdani, Ilham; Alamsyah , Sakti; Nugroho, Gatot Wahyu (Journal of Management, Economic, and Accounting, 2023)
This thesis research was carried out at the Sukabumi City Disporapar. The purpose of this writing is to determine the effect of budget planning and budget evaluation on performance accountability in the Sukabumi City Disporapar. The variables used are Budget Planning and Budget Evaluation as Independent Variables and Performance Accountability as Dependent Variables. The research method used is Quantitative with associative type. The scale of measurement used is the ordinal scale. The population used is the employees associated with the planning and finance section of the Sukabumi City Disporapar, with a purposive sampling technique. the number of samples is 40 employees. the types of data used are primary and secondary data. The data collected was analyzed using validity and reliability tests, data quality tests, classic assumption tests, hypothesis testing, namely the t test, F test and the coefficient of determination test. The results showed that in the independent variable validity test, 14 statements were declared valid, and the dependent variable contained 6 valid statements. the results of the reliability test show that the independent and dependent variable instruments are reliable. the results of testing the hypothesis show that budget planning and budget evaluation have a significant positive effect on performance accountability. and the results of the test of the coefficient of determination of the budget planning and budget evaluation variables are able to explain the performance accountability variable. The results showed that of the budget planning and budget evaluation had a significant positive impact on performance accountability at the Sukabumi City Disporapar. based on the results of the calculation of the coefficient of determination, it is obtained that the magnitude of the impact of budget planning and budget evaluation on performance accountability is 72.2%. while the remaining 27.8% is influenced by other factors not examined.